2019
DOI: 10.1080/10871209.2019.1619883
|View full text |Cite
|
Sign up to set email alerts
|

A framework of most effective practices in protecting human assets from predators

Abstract: Widespread damage by large mammalian predators to human assets (e.g., livestock, crops, neighborhood safety) requires the application of non-invasive (i.e., without direct contact with predators) and targeted interventions to promote predator conservation and local livelihoods. We compiled 117 cases from 23 countries describing the effectiveness of 12 interventions designed to protect human assets from 21 predators. We found: (a) the most effective interventions were electric fences, guarding animals, calving … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
56
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 36 publications
(56 citation statements)
references
References 49 publications
0
56
0
Order By: Relevance
“…Still, we find these measures promising and suggest scientists and practitioners to invest more effort into their application and effectiveness estimation. Calving control means shortening the calving season to several months and limiting calf accessibility to open grazing grounds 36 . As calves and other juveniles of livestock constitute most losses, reducing the period of calf availability keeps losses down 25 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Still, we find these measures promising and suggest scientists and practitioners to invest more effort into their application and effectiveness estimation. Calving control means shortening the calving season to several months and limiting calf accessibility to open grazing grounds 36 . As calves and other juveniles of livestock constitute most losses, reducing the period of calf availability keeps losses down 25 .…”
Section: Discussionmentioning
confidence: 99%
“…It was found that guarding dogs and llamas are effective against brown bears and American black bears 35 . The largest bear samples compiled in studies 32 , 36 showed that the effectiveness of interventions varied greatly between study areas and within ursid species, making it hard to reveal species-specific and general patterns. Due to these limitations, so far it was impossible to find the most effective and the least effective interventions against bears and to compare the effectiveness of non-invasive interventions, invasive management and lethal control.…”
Section: Introductionmentioning
confidence: 99%
“…Lethal control can, for example, alter carnivore social structure and cause more individuals to migrate, take over and start depredating in an area, thus exacerbating a problem rather than solving it [12,135]. Predator controls that have not been proven to be effective should not be used and more studies need to be carried out to determine the best ways to approach different conflict scenarios [14].…”
Section: Discussionmentioning
confidence: 99%
“…A seal blind is the area at the bottom of the net where a thicker square of netting material conceals dead fish from seals approaching the net from underneath [74]. Khorozyan and Waltert also found controls around calving to be important for reducing conflict [14]. Afterbirth can attract carnivores and so it is necessary to plan the timing and location of calving [65].…”
Section: Habitat Use and Management Factorsmentioning
confidence: 99%
See 1 more Smart Citation